Application of Analysis of Strengths, Weaknesses, Opportunities, and Threats in Islamic Education Institutions - Ava Swastika Fahriana; Miftachul Huda (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) is carried out by educational institutions to assess the strengths and weaknesses of the institution before setting goals and outlining achievement goals, which is a logical consequence that must be taken by educational institutions to operate smoothly. Strength and weakness tests are internal audits of how effective the institution's performance is. While opportunities and threats concentrate on the external context or environment in which an institution operates. The SWOT analysis aims to find essential aspects of things such as strengths, weaknesses, opportunities, threats. The purpose of this test is to maximize power, minimize weaknesses, reduce risks and build opportunities. Recognizing strengths, weaknesses, opportunities, threats and continuing to reflect is a step towards advancing for Islamic educational institutions. Analisis SWOT (Strengths, Weaknesses, Opprtunities, and Threats) dilakukan oleh lembaga pendidikan untuk mengkaji kekuatan dan kelemahan pada lembaga tersebut sebelum menentukan tujuan dan menggariskan tindakan pencapaian tujuan, yang merupakan konsekuensi logis yang perlu ditempuh lembaga pendidikan agar supaya lancar di dalam operasionalnya. Uji kekuatan dan kelemahan pada dasarnya merupakan audit internal tentang seberapa efektif performa institusi. Sementara peluang dan ancaman berkonsentrasi pada konteks eksternal atau lingkungan tempat sebuah isntitusi beroperasi. Analisis SWOT bertujuan untuk menemukan aspek-aspek penting dari hal-hal kekuatan, kelemahan, peluang, ancaman. Tujuan pengujian ini adalah untuk memaksimalkan kekuatan, meminimalkan kelemahan, mereduksi ancaman dan membangun peluang. Mengenali kekuatan, kelemahan, peluang, ancaman dan terus melakukan refleksi adalah sebuah langkah bersar untuk menuju kemajuan bagi lembaga pendidikan Islam.